The historical approach of Dr. Abdul Aziz Al Duri Studies in the late Abbasid period are a model. - Farhan Zuair, Ali (Journal of College of Education, 2019)
The historical facts of the historians have been dealt with in terms of accuracy, analysis, comprehensiveness and vision from one angle. This research seeks to identify the efforts of Dr. Abdul Aziz Al-Douri, that is, the shift from the study of historical events to the study of the authors. The historical approach has, and how it was able to preview the political, economic and social conditions, we include in his book "Studies in the late Abbasid times," through which we proposed to the three pre-foreword and the results of the introduction, and the first topic was held to study the political situation in its methodology, What the second topic has fought in the impact of economic conditions in the Zinj revolution, while the third section engaged in representations of historical and social writing when Dr. Abdul Aziz al-Douri, has demonstrated the difficulties that the league was adopted on the establishment and deduction of his method,
Keywords: Abbasid ages , Historical Social Writing , The political situation